The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.697168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain Atlases and Machine Learning Methods on the Discrimination of Schizophrenia Patients: A Multimodal MRI Study

Abstract: Recently, machine learning techniques have been widely applied in discriminative studies of schizophrenia (SZ) patients with multimodal magnetic resonance imaging (MRI); however, the effects of brain atlases and machine learning methods remain largely unknown. In this study, we collected MRI data for 61 first-episode SZ patients (FESZ), 79 chronic SZ patients (CSZ) and 205 normal controls (NC) and calculated 4 MRI measurements, including regional gray matter volume (GMV), regional homogeneity (ReHo), amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 92 publications
2
18
0
Order By: Relevance
“…Previous studies of SZ patients have shown different classification performances using different dimensionality reduction algorithms ( Li et al, 2015 ; Winterburn et al, 2019 ). Third, we have used different brain atlases in the discriminative analysis of SZ patients based on neuroimaging features and revealed that the 268-node functional atlas outperformed the other two brain atlases ( Zang et al, 2021 ). However, it is necessary to compare the effects among different combinations of dimensionality reduction algorithms and brain atlases from the perspective of brain network properties in future studies.…”
Section: Limitations Of the Methodologymentioning
confidence: 99%
“…Previous studies of SZ patients have shown different classification performances using different dimensionality reduction algorithms ( Li et al, 2015 ; Winterburn et al, 2019 ). Third, we have used different brain atlases in the discriminative analysis of SZ patients based on neuroimaging features and revealed that the 268-node functional atlas outperformed the other two brain atlases ( Zang et al, 2021 ). However, it is necessary to compare the effects among different combinations of dimensionality reduction algorithms and brain atlases from the perspective of brain network properties in future studies.…”
Section: Limitations Of the Methodologymentioning
confidence: 99%
“…The preprocessing steps of multimodal MRI data were same to those in our previous studies ( Wu et al, 2018 ; Kong et al, 2021 ; Zang et al, 2021 ). More details were described in the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%
“…Second, our MRI measures were all calculated based on the Brainnetome atlas (Fan et al, 2016). The choice of brain atlases should not be arbitrary, since it could lead to different results such as in discrimination analysis (Zang et al, 2021). Although we employed a fine-grained parcellation, which contains information on both anatomical and functional connections, comparisons between various brain atlases need to be accomplished.…”
Section: Discussionmentioning
confidence: 99%